Implementação de estruturas EBG em antenas de microfitas e polarização linear-circular com metasuperfície para WLAN - Silva, José Lucas da (2018)
With the wide use of wireless communication systems and its application in Wireless Local Area Network (WLAN) frequency band, the present work aims to analyze the behavior of microstrip antennas, designed in configurations of structures with resonator rings (SRR), resonators (CSRRs) and banned electromagnetic bands (EBG) with bandwidth above 400 MHz. These elements are periodically inserted under the patch on the antennas substrate and developed for ISM frequency bands - bands reserved for industrial, scientific and medical development (2.45 GHz and 5.85 GHz). Hence, the objective is to improve the performance of the electromagnetic parameters of these modern microstrip antennas. Then, the proposed antennas are applied to the simplified cell metasurface model, in order to provide the ability to convert the linearly polarized signals generated by a microstrip antenna into circularly polarized signals, obeying their projected operating range. To obtain optimization of the structures modeled in the polarization according to the response of frequency band, axial ratio and desired return loss, the optimetric tool was used, allowing to exploit results for return loss of less than -10 dB and axial ratio below 3 dB. The numerical analysis of the structures takes place through ANSYS HFSS and, to validate these results, the structures will be experimentally characterized.